That time I loved you : stories - Leung, Carrianne (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2019)
The residents of a new subdivision in 1970s Toronto are torn by a rash of suicides that are linked to dark undercurrents of infidelity, racism, and hidden abuse.